Application of the Principles of Anti-Oppression to Address Marginalized Students and Faculty’s Experiences in Counselor Education - Afroze N Shaikh; Sravya Gummaluri; Jyotsna Dhar; Hannah Carter; Daun Kwag; Javier E Ponce; Erin C. M. Mason; Harvey C Peters (Teaching and Supervision in Counseling, 2024)
Despite efforts to decolonize and diversify the counseling profession, individuals with marginalized identities continue to encounter harmful experiences, requiring urgent and intentional action by counselor education programs to respond to these challenges. Recent legislative efforts have had a detrimental impact on marginalized communities, including those who identify on the spectrum of womanhood, immigrants, people of color, lesbian, gay, bisexual, transgender, queer and/or questioning, intersex, asexual, and/or two-spirit (LGBTQIA2S+), emphasizing pre-existing forces of power, privilege, and oppression embedded in academia. In search of a liberatory framework to address these forces, the authors apply Peters and Luke's (2022) Principles of Anti-Oppression to address eight common adverse experiences identified by Thacker and Barrio Minton (2021) that students and faculty with marginalized identities encounter in counselor education.
Keywords: anti-oppression; decolonization; counselor education; marginalization; diversity